American city St. Louis architecture : three centuries of classic design - Sharoff, Robert (American city series)
Features Louis Sullivan's Wainwright Building, Alfred Mullet's Old Post Office and Theodore Link's Union Station, Eero Saarinen's Gateway Arch, Tadao Andao's Pulitzer Foundation for the Arts Building and Maya Lin's recently completed Ellen Clark Hope Plaza.